Question: After a free falling sky diver of mass $m$ reaches a constant velocity of $v_1$, her parachute opens, and the resulting air resistance force has strength $Kv$. Once the parachute opens, the equation of motion is

$$ \frac {dv}{dt} = g - Bv $$

where $ B = \frac Km $, $K$ is the constant of proportionality and $g$ denotes the value of gravitational acceleration.

Show that the equation for the speed of the sky diver $t$ seconds after the parachute opens is

$$ v = \frac{mg}{K} \left[ {1} + ({\frac{K}{mg}v_1 - 1)e^{-{Kt\over m}}} \right] = 0$$

What I have done:

$$ \frac{dv}{dt} = g-Bv $$

$$ \int \frac{1}{g-Bv} dv = \int dt $$

$$ -\ln|g-Bv| \cdot \frac{1}{B} = t + Bc$$

$$ g-Bv = Ae^{-Bt}$$

$$ g-Ae^{-Bt} = Bv $$

$$ {g-Ae^{-Bt}\over B} = v$$

When $t$ $=$ $0$ , $v$ $=$ $v_1$

$$ {g-A\over B} = v_1$$

$$ A = g-Bv_1 $$

$$ v = {g-Ae^{-Bt}\over B} $$

$$ v= {g-(g-Bv_1)e^{-Bt}\over B} $$

$$ v= {g+(Bv_1-g)e^{-Bt}\over B} $$

But $ B = \frac Km $

$$ v= {mg+({K\over m}v_1-g)e^{-({K\over m})t}\over K} $$

Now am I stuck...

  • $\begingroup$ In the last expression you obtained, the $m$ needs to multiply the bracketed term as well, then you have the result you want. $\endgroup$ – David Quinn Jan 29 '16 at 21:09

From $$v={g+(Bv_1-g)e^{-Bt}\over B}$$ and using $$B=\frac{K}m$$ we get $$v={g+(\frac{K}mv_1-g)e^{-\frac{K}mt}\over \frac{K}m}$$ Multiplying top and bottom by $m$ gives $$v={m(g+(\frac{K}mv_1-g)e^{-\frac{K}mt})\over K}$$ Multiply the $m$ through the bracket in the numerator $$v={mg+(Kv_1-mg)e^{-\frac{K}mt})\over K}$$ and remove the 'common' factor of $mg$ $$v={mg(1+(\frac{K}{mg}v_1-1)e^{-\frac{K}mt})\over K}$$ and identify $K$ with $mg$ $$v=\frac{mg}K\left[1+(\frac{K}{mg}v_1-1)e^{-\frac{K}mt}\right]$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.